EVALUASI KEMAMPUAN MANAJER INVESTASI REKSADANA SAHAM BERDASARKAN MARKET TIMING DAN STOCK SELECTION SKILL - Amanda Widya Kharisma; Felix Wisnu Isdaryadi (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2017)
AbstractThis study aimed to evaluate whether the investment manager of mutual funds in Indonesia has the ability to market timing and stock selection or not. The data used in this study was obtained from the data of NAV per unit of active mutual funds listed on the Indonesia Stock Exchange, the interest rate of Bank Indonesia, and the Jakarta Composite Index monthly period January 2011 until December 2015.Purposive sampling have been use to select the samples resulted in fiveteen mutual fund shares listed and active in Bapepam-LK during the period January 2011 to December 2015. The model used is the Mazuy Treynor Model (1966). Based on Mazuy Treynor Model, regressed among Excess Return Fund as the dependent variable, and QuadraticExcess Excess Market Return Market Return as independent variables.The results showed that from the fiveteen mutual funds have been studied, no investment manager who has the ability to market timing. This is evidenced by the absence coefficient γ as a positive indicator of market timing is significant. Stock selection ability of the fiveteen equity funds examined solely owned by two investment managers, namely “Batavia Dana Saham Optimal” and “Pratama Ekuitas”. This is evidenced by the coefficient α as an indicator of stock selection both positive investment managers are significant. Keywords: investment managers, market timing ability, Net Asset Value, stock selection skills